Efeito adicional do butirato de sódio na alimentação de leitões - Caxias Junior, Osiris Antunes de (2016)
This study aimed to evaluate the performance, the incidence of diarrhea and rectal microbiological profile in piglets in nursery phase fed diets with and without the addition of sodium butyrate 30% coated. For that, 80 crossbred commercial barrows and gilts were used, with average weight of 9.47 (1.03) kg, in a randomized complete block design with four treatments repeated twice in both blocks, and five pigs of same sex by each experimental unit. Treatments consisted in a combination of two experimental diets with and without inclusion of sodium butyrate coated as a supplementary product to the diet, and both sexes. The experimental diets were based on corn and soybean meal and were added or not 0.1% of sodium butyrate 30% coated to the diets from diet pre-initial I. The final body weight, daily weight gain, daily feed intake and feed conversion were evaluated. There was no significant effect of product tested on animal performance. There was a significant effect (p=0.05) of sodium butyrate in the incidence of diarrhea, where pigs fed diets containing sodium butyrate had lower rates of diarrhea than pigs who did not receive the product. Rectal microbiological profile was determined by quantitative analysis of Escherichia coli, Clostridium sulfite reducers and lactic acid bacteria having reduced count of E. coli from 14th to 28th day but no effect on other microorganisms evaluated. The blood parameters measured in two animals of each experimental unit have been within the normal physiological parameters of the species. The addition of sodium butyrate coated 30% did not affect the performance of piglets in nursery phase in experimental environment with reduced health challenges, however, it was effective in reducing diarrhea-causing gastrointestinal disorders